2022
DOI: 10.3390/jcm11102895
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Hysteresis, Intraocular Pressure, and Progression of Glaucoma: Time for a “Hyst-Oric” Change in Clinical Practice?

Abstract: It is known that as people age their tissues become less compliant and the ocular structures are no different. Corneal Hysteresis (CH) is a surrogate marker for ocular compliance. Low hysteresis values are associated with optic nerve damage and visual field loss, the structural and functional components of glaucomatous optic neuropathy. Presently, a range of parameters are measured to monitor and stratify glaucoma, including intraocular pressure (IOP), central corneal thickness (CCT), optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 80 publications
(76 reference statements)
2
9
0
2
Order By: Relevance
“…[11][12][13] Otherwise, several studies have suggested that patients with ocular hypertension (OHT) but no glaucomatous changes showed less deformable corneas. 9,10,[14][15][16] These corneal biomechanical differences indicate that the appearance and progression of glaucoma could be associated with specific corneal biomechanical DOI: 10.1097/IJG.0000000000002170 changes, 17,18 which may offer a novel perspective on glaucoma pathology.…”
mentioning
confidence: 99%
“…[11][12][13] Otherwise, several studies have suggested that patients with ocular hypertension (OHT) but no glaucomatous changes showed less deformable corneas. 9,10,[14][15][16] These corneal biomechanical differences indicate that the appearance and progression of glaucoma could be associated with specific corneal biomechanical DOI: 10.1097/IJG.0000000000002170 changes, 17,18 which may offer a novel perspective on glaucoma pathology.…”
mentioning
confidence: 99%
“…In addition, reduced CH means that the optic nerve head is less deformable, meaning that its damping ability is smaller, resulting in a firmer less flexible lamina cribrosa [44]. Furthermore, it has been shown that the lower the corneal hysteresis, the greater the cup/disc ratio [42,43]. Therefore, CH is now accorded high importance in glaucoma diagnostics.…”
Section: Corneal Biomechanicsmentioning
confidence: 99%
“…Zudem bedeutet eine verminderte CH, dass der Sehnervenkopf weniger verformbar ist und somit seine Dämpfungskapazität kleiner ist, was eine festere, wenig nachgiebige Lamina cribrosa bedingt [44]. Weiterhin wurde gezeigt, dass je niedriger die korneale Hysterese ist, desto größer ist die Cup-Disk-Ratio [42,43]. Insofern wird der CH heute in der Glaukomdiagnostik ein hoher Stellenwert zugeordnet.…”
Section: Korneale Biomechanikunclassified
See 1 more Smart Citation
“…The identification of markers helping in the early glaucoma diagnosis and detection of subtle signs of disease progression is a fascinating field of investigation. In the review article, Murtagh and O'Brien [22] summarize the current knowledge about corneal hysteresis (CH). CH is a relatively new ocular parameter provided by two devices available on the market, which include the Ocular Response Analyzer tonometer (ORA) and the Corneal Visualization Scheimpflug Technology tonometer (Corvis ST).…”
mentioning
confidence: 99%